Tacrolimus time‐in‐therapeutic range is associated with freedom from acute rejection and graft failure following intestinal transplantation. Issue 6 (3rd April 2021) - Santeusanio, Andrew D.; Gu, Alan; Weinberg, Alan D.; Moon, Jang; Iyer, Kishore R.
Abstract: Background: Trough‐adjusted tacrolimus is commonly prescribed following intestinal transplantation to prevent allograft rejection. Despite established practice, there remains limited direct evidence linking tacrolimus levels with improved clinical outcomes. Methods: This was a single‐center review of all adult non‐liver containing intestinal allograft recipients from 2011 to 2018. Patients received lymphocyte depleting induction and maintenance immunosuppression consisting of tacrolimus and a corticosteroid taper. Tacrolimus time‐in‐therapeutic range (TAC‐TTR) was calculated for all patients from the date of transplant until 1‐year post‐transplant using Rosendaal's method. Cox‐Proportional hazards modeling was utilized to assess freedom from acute rejection and graft failure stratified by TAC‐TTR quartile. Results: 47 patients were included in the review. Mean TAC‐TTR for the cohort was 30.2% ± 11.4. Fifteen episodes of acute rejection were observed, 8 of which were severe. Patients in the highest TAC‐TTR quartile >36% had a lower incidence of acute rejection and graft failure relative to patients with a TAC‐TTR <20%. Cox‐Proportional hazards modeling found a 10% decrease in TAC‐TTR was associated with an increased hazard for acute rejection (2.03), severe acute rejection (2.19), and graft loss (3.33). Conclusion: The results of this study suggest that decreasing TAC‐TTR is a risk factor for both acute rejection as well as intestinal allograft failure.